Oxytocin administration for induction and augmentation of labour in Polish maternity units - an observational study - Daly, Deirdre (My University, 2021)
Background: There is not enough data regarding practices and protocols on the dose of oxytocin administrated to women during labour. Empirical evidence indicates that compliance with the guidelines improves the quality of healthcare and reduces adverse effects. The study aimed to evaluate practices of oxytocin provision for labour induction and augmentation in two maternity units in Poland. Methods: The article presents a prospective observational study. Data from 545 (n = 545) labours was collected in two maternity units. First, the total dose (the total amount of oxytocin provided from the beginning in the labour ward until delivery including the III and IV stage of labour) and cumulative dose of oxytocin (the amount of oxytocin given until the birth of the neonate) administered to women during labour was calculated. Then, the relationship between the cumulative dose of oxytocin and short term perinatal outcomes (mode of delivery, use of epidural anaesthesia, Apgar scores, birth weight and postpartum blood loss) was analysed. Finally, the compliance of oxytocin supply during labour with national guidelines in the following five criteria: medium, start dose, escalation rate, interval, the continuation of infusion after established labour was examined. Results: The average cumulative dose of oxytocin administrated to women before birth was 4402 mU following labour induction and 2366 mU following labour augmentation. The actual administration of oxytocin deviated both from the unit and national guidelines in 93.6% of all observed labours (mainly because of continuation of infusion after established labour). We found no statistically significant correlation between the cumulative dose of oxytocin administered and mode of delivery, immediate postpartum blood loss or Apgar scores. There was no observed effect of cumulative dose oxytocin on short‑term perinatal outcomes. The two units participating in the study had similar protocols and did not differ significantly in terms of total oxytocin dose, rates of induction and augmentation ‑ the only observed difference was the mode of delivery. Conclusions: The study showed no effect of the mean cumulative oxytocin dose on short‑term perinatal outcomes and high rate of non‑compliance of the practice of oxytocin administration for labour induction and augmentation with the national recommendations. Cooperation between different professional groups of maternity care providers should be considered in building national guidelines for maternity care. Further studies investigating possible long‑term effects of the meant cumulative dose of oxytocin and the reasons for non‑compliance of practice with guidelines should be carried out.
PUBLISHED
Keywords: Oxytocin; Labour; Induction; Augmentation; Practice protocol; Augmentation of labour; Childbirth/Labour/Intrapartum; Clinical practice protocol; Induction of labour; LABOUR; OXYTOCIN; OXYTOCIN INFUSION; Health